Fruit and vegetable intake of mothers of 11-year-old children in nine European countries: The Pro Children Cross-sectional Survey - Wolf, Alexandra; Yngve, Agneta; Elmadfa, Ibrahim; Poortvliet, Eric; Ehrenblad, Bettina; Pérez-Rodrigo, Carmen; Thorsdottir, Inga; Haraldsdottir, Johanna; Brug, Johannes; Maes, Lea; Vaz de Almeida, Maria Daniel; Krølner, Rikke; et al. (Annals of Nutrition and Metabolism, 2006)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field OBJECTIVE: To describe and compare fruit and vegetable intakes of mothers of 11-year-old children across Europe. METHODS: Cross-sectional surveys were carried out in 9 European countries in October/November 2003. Self-administered questionnaires assessing fruit and vegetable consumption were used for data collection. The current paper presents dietary intake data obtained by a precoded 24-hour recall and a food frequency questionnaire. RESULTS: The consumption levels of fruit and vegetables (without fruit juice) were in line with World Health Organization recommendations of > or =400 g/day for only 27% of all participating mothers. Based on both instruments, the Pro Children results showed comparatively high average fruit intake levels in Portugal, Denmark and Sweden (211, 203 and 194 g/day) and the lowest intake in Iceland (97 g/day). High vegetable intake levels were found in Portugal and Belgium (169 and 150 g/day), the lowest in Spain (88 g/day). A south-north gradient could not be observed in the Pro Children study. CONCLUSION: Fruit and vegetable intakes are low in mothers of 11-year-olds across Europe. Especially vegetable consumption can be regarded as marginal in most of the studied European countries. A high percentage of mothers indicated to eat fruit and vegetables less than once a day. The results have shown that national and international interventions are necessary to promote fruit and especially vegetable consumption in the European population of mothers.